Analysis Of The Impact Of Information And Communication Technologies On Accounting Systems (Journal of Pharmaceutical Negative Results, 2023)
The objective of this research work is to publicize the impact of information and communication technologies on business accounting systems. At present, due to economic changes characterized by levels of competitiveness, high quality in the provision of goods and services, it is necessary and essential to have mechanized and automated tools that provide accounting and financial information that is timely, reliable and truthful. In order to facilitate decision-making in relation to their entities to the various stakeholders, for which it is essential to determine the importance of Information and Communication Technologies and how they influence business accounting systems. The study was carried out in the accounting systems of the Chimbote fishing companies, with a sample of 15 entities during the year 2022.